A multi-taxonomic survey to determine the conservation status of native pollinators - Schlesinger, Matthew D.; White, Erin L.; Corser, Jeffrey D.; Danforth, Bryan N.; Fierke, Melissa K.; Greenwood, Carmen M.; Hatfield, Richard G.; Hietala-Henschell, Katie G.; Mawdsley, Jonathan R.; McFarland, Kent P.; Niver, Robyn; Rozen, Jerome G.; et al. (Frontiers in Ecology and Evolution, 2023)
The worldwide decline of insects calls for understanding the conservation status of key insect groups at local and regional scales. Pollinators are widely recognized as especially important to native ecosystems and agriculture and their declines have been met with calls for inventory and monitoring. In New York State, we conducted a four-year survey effort to document the distribution and status of key native pollinators in four insect orders: Coleoptera, Diptera, Hymenoptera, and Lepidoptera. In this paper, we describe the process of designing and implementing the study in the hopes that other jurisdictions could follow a similar model. We combined systematic field inventories, surveys of special habitats, target species surveys, community science observations, and museum and partner data to create a comprehensive look at the distribution of each of 457 species in two time periods (2000 to present and 1999 and earlier). We used the conservation status ranking system developed by NatureServe and generated ranks and a series of distribution maps and phenology charts for each species. We describe the effort needed to carry out the study, as well as reasons for its success and areas for improvement.